1992
DOI: 10.1103/physreva.45.2520
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and diagnostics of the structure of rf glow discharges in Ar at 13.56 MHz

Abstract: The structure of rf glow discharges in Ar at 13.56 MHz is described, making use of a relaxation continuum model. The model includes consideration of the relaxation kinetics for the momentum and energy of charged particles. The discharge structure and plasma property are modeled using molecular quantities (i.e. , collision cross sections, radiative lifetimes, etc.) and macroscopic transport quantities for charged particles. Spatiotemporal distributions for the field and the net production rate and density of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(66 citation statements)
references
References 85 publications
1
65
0
Order By: Relevance
“…results which follow directly from (25), (26), (32) and the relationships (34). The distinction between two sets of transport coefficients vanishes when either R=0 or when the reactive cross sections are not energy selective [13,38].…”
Section: Periodic Steady State and Transport Coefficients (I) Densitymentioning
confidence: 98%
See 2 more Smart Citations
“…results which follow directly from (25), (26), (32) and the relationships (34). The distinction between two sets of transport coefficients vanishes when either R=0 or when the reactive cross sections are not energy selective [13,38].…”
Section: Periodic Steady State and Transport Coefficients (I) Densitymentioning
confidence: 98%
“…This set of equations is sufficient to determine``flux'' transport coefficients [38] w, D | | and D = for specified field frequency and cross sections.``Bulk'' transport coefficients [38] (B) W, (B) D | | and (B) D = , as given by (34), require a second order density gradient expansion (c.f. (31)) and are dealt with in [42].…”
Section: Nonuniform Swarms: Electron Diffusion Coefficients (I) Basicmentioning
confidence: 99%
See 1 more Smart Citation
“…The theory, at its lowest level, is similar in spirit to the 'relaxation continuum' model of Makabe et al (1992), but the origin and definition of the collisional relaxation times is more precise. In essence, momentum-transfer theory provides a scheme for systematic approximation of collision terms in moment equations generated by integrating Boltzmann's equation for each charged species with 1, mv,~mv2, ... over all particle velocities v. In the lowest approximation, momentum-transfer theory consists in employing collision terms of the same mathematical form as for the Maxwell (constant collision frequency) model, but with cross sections evaluated according to actual energy dependencies.…”
Section: Rf Swarm Model Equations (2a) Momentum-transfer Theory Bamentioning
confidence: 97%
“…Additional interesting results in the research of production and properties of negative ions in Ar/CF 4 can be found (for example, in [10][11][12]). …”
Section: Introduction and State Of The Artmentioning
confidence: 98%